Participatory systems mapping as relational (but not relational enough) method for evaluating complex social phenomena - Rossi, Paula; Husso, Kyösti; Jalonen, Harri (Routledge, 2026)
This article addresses participatory systems mapping (PSM) as a relational method for evaluating complex social phenomena by utilizing an illustrative case example related to young people’s wellbeing in schools and at work. Theoretically grounded in complexity thinking and analysing the data produced in participatory workshops through the public service ecosystem (PSE) framework, the article contributes by foregrounding the systemic and relational understanding of the phenomena studied as a basis for public policy evaluation. Through participatory processes and the chosen analytical framework, the PSM method identifies and visualizes key leverage points, clusters of leverage points, and their relationships across the individual, organizational, and institutional spheres of the system. Targeting actions to these leverage points can improve young people’s wellbeing. In practice, relational aspects such as situational awareness and flexibility, particularly concerning power dynamics and participant diversity, become important when using the PSM method.
Keywords: Complexity; education; mental health; participatory systems mapping (PSM); public policy; relational evaluation; young people; working life; fi=Julkisjohtaminen|en=Public Management|; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|